2020
DOI: 10.3389/fcell.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

A New World of Biomarkers and Therapeutics for Female Reproductive System and Breast Cancers: Circular RNAs

Abstract: As one of the most recently (re)discovered types of non-coding RNAs (ncRNA), circular RNAs (circRNAs) differentiate from other ncRNAs by a specific biogenesis, high stability, and distinct functions. The biogenesis of circRNAs can be categorized into three mechanisms that permit the back-splicing reaction: exon-skipping, pairing of neighboring introns, and dimerization of RNA-binding proteins. Regarding their stability, circRNAs have no free ends, specific to linear RNA molecules, prompting a longer half-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 165 publications
(173 reference statements)
0
54
0
Order By: Relevance
“…Cervical cancer, as one of the common human tumors, is one of the most common gynecological malignancies, [1][2][3][4][5]34 which is like other tumors [35][36][37][38][39][40][41] and they threatened seriously to human health as well as cervical cancer, [42][43][44][45][46][47][48] its morbidity and mortality rate are at the forefront of female malignancies. Surgery, radiotherapy and chemotherapy for early cervical cancer have good effects, but in advanced stage, the therapeutic effect of metastatic and recurrent cervical cancer is very limited and the survival rate is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer, as one of the common human tumors, is one of the most common gynecological malignancies, [1][2][3][4][5]34 which is like other tumors [35][36][37][38][39][40][41] and they threatened seriously to human health as well as cervical cancer, [42][43][44][45][46][47][48] its morbidity and mortality rate are at the forefront of female malignancies. Surgery, radiotherapy and chemotherapy for early cervical cancer have good effects, but in advanced stage, the therapeutic effect of metastatic and recurrent cervical cancer is very limited and the survival rate is low.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is considered to be one of the most common gynecological malignant tumors in the world and highly occurred in developing countries, [1][2][3][4][5] which is a serious threat to women's health. Globally, cervical cancers rank the fourth one among female tumor causes of death and the incidence of cervical cancer ranks the first one among female genital malignancies in China.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of these 20 circRNAs have never been reported before, and we speculated that their dysregulation might be specific for PTB. The remaining 9 circRNAs have been demonstrated to be correlated with breast cancer (hsa-SCARF1_0001), osteoarthritis (hsa-GCN1_0003), osteosarcoma (hsa-RAD54L2_002), virus infection (hsa-CREBBP_0001), ovarian cancer (hsa-FAM13B_0019), hepatocellular carcinoma (hsa-NUSAP1_0010), endometrial cancer (hsa-YY1AP1_0001), hypopharyngeal squamous cell carcinoma (hsa-MORC3_0001), and gestational diabetes mellitus (hsa-RANBP9_0002) (Fu et al, 2018;Kun-Peng et al, 2018;Hu et al, 2019;Li et al, 2019;Lou et al, 2019;Wang et al, 2019Wang et al, , 2020Guo et al, 2020;Tran et al, 2020). Interestingly, we found that all these diseases shared a common pathological ground of inflammation and immune activation with PTB, which happens to be the main way that the selected circRNAs regulate these diseases (Cappelletti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…20 Some cir-cRNAs have been verified as latent therapeutic targets and novel biomarkers in a series of diseases, including tumors. 21 A previous report revealed that circRNA circ_KDM4C moderated doxorubicin resistance and impeded tumor growth in BC through increasing PBLD expression by sponging miR-548p. 22 Also, circRNA hsa_circ_0009362, 23 circRNA circ_TFF1, 24 and circRNA circ_circACAP2 25 contributed to the advancement of BC.…”
Section: Discussionmentioning
confidence: 99%